Control Sets of Linear Control Systems on Matrix Groups and Applications. (4th July 2019) - Ayala, Víctor; Román-Flores, Heriberto; Torreblanca Todco, María
Abstract : We review recent results on control sets of linear control systems on matrix groups. We also mention some applications of systems with algebraic structures.